Islam and the Challenge of Economic Development in the Muslim World: Review and Evaluation of Secular Arguments - Abdelrahman, Abdelrahman Yousri (Intellectual Discourse, 2018)
The majority of Muslim countries, classified as low or middle income groups, suffer from poverty and face severe challenges in economic development. International development reports attribute the economic problems of Muslim countries to similar factors as those existing in other developing countries. However, some secular studies have analyzed the impact of Islamic culture on the economic variables in the Muslim World, and consequently on its economic development. This paper reviews and evaluates some of these studies. Secular works which are selected and examined in this article can be classified into two main groups. The first group makes no distinction between authentic Islamic culture and contemporary culture which is prevailing in Muslim countries and builds its analysis and conclusion upon this misconception. The second group, however, raises objections towards some specific Islamic laws and traditional rules, considering them among factors which have hindered economic development in the Muslim world.